Consumer Behaviour and Sustainable Fashion Consumption - Muthu, Subramanian Senthilkannan; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2019)
This book analyses the importance of consumer behaviour in sustainable fashion and consumption. Consumer behaviour plays a major role in sustainability, and when it comes to textile products, a number of studies have shown that for certain product categories, consumer behaviour during use and disposal stages influences the entire life cycle impacts of the product more than the raw material and manufacturing stages. However green the production, the overall sustainability of a product depends on the consumers who use and dispose of it.
Sustainable Fashion Sportswear Consumption -- Analysing the Consumer Behavior Regarding Sustainable Fashion Using Theory of Planned Behavior -- The Impact of Knowledge on Consumer Behaviour Towards Sustainable Apparel Consumption.
Keywords: Manufactures; Sustainability; Business logistics; Industrial engineering; Production engineering; Consumer behavior; Machines, Tools, Processes; Sustainability; Supply Chain Management; Industrial and Production Engineering; Consumer Behavior